Influence of Atmospheric Ammonia on Serum Corticosterone, Estradiol-17β and Progesterone in Laying Hens - Edens , Frank W. (International Journal of Poultry Science, 2015)
Hormonal profiles of hens in curtain side-walled high-rise deep pit and flush-waste layer houses were initiated at placement of hens in cages in August and continued through a 50 weeks long laying trial. In mid-January, a cold weather-related incident caused the rupture of water lines and flooding of the manure pits in the deep pit layer house, allowing atmospheric ammonia to rise to a high of 135±29 ppm and remain high through mid-February when the pits were finally emptied. After removal of wet manure from the deep pit, atmospheric ammonia in the deep pit house decreased to 25±9 ppm compared to 21±4 ppm in the flush-waste house. Elevated atmospheric ammonia in the deep pit house caused the hens, compared to hens in the flush-waste house, to increase significantly (p